Waves and structural strain induced by a uniform current flow underneath a semi-infinite floating solar coverage - Yang, Yifeng; Huang, Luofeng (American Physical Society, 2024)
Floating solar panels installed on water reservoirs will be an increasingly popular renewable energy scenario. However, a significant current flow will occur when the reservoir gate is open to release water. Such a current flow can cause complex fluid-structure interaction at the edge of the solar panels, reversely analogized to a ship advancing through calm water, signifying the generation of a stern wave. This wave can damage the solar panels, which needs to be investigated to ensure operational safety. In this context, the present paper analyzes a mixed boundary problem of a uniform flow passing through a two-dimensional semi-infinite elastic plate using an analytical approach—the Wiener-Hopf technique. The mathematical model is based on the linearized velocity potential for fluid flow and the Kirchhoff-Love plate theory for an elastic plate. Three different edge conditions are considered here, namely, clamped, simply supported, and free. Extensive results and discussions are provided for the amplitudes of the propagation wave, and principal strain in the elastic thin plate. In particular, significant “resonance” fluid-structure interactions are found when the current speed is at certain special magnitudes. To support straightforward industrial applications, these special flow rates are given as a water depth Froude number. Overall, this study can provide valuable insights for floating solar projects on water reservoirs to control the water-release rate, thus minimizing the potential structural problems.
Keywords: 4012 Fluid mechanics and thermal engineering; floating solar; water reservoir; semi-infinite elastic plate; uniform current; Wiener-22 Hopf technique; resonance.